2012
DOI: 10.5430/jnep.v2n2p41
|View full text |Cite
|
Sign up to set email alerts
|

Public home care professionals’ experiences of being involved in food distribution to home-living elderly people in Sweden – a qualitative study with an action research approach

Abstract: Background: Research focusing on Food Distribution (FD) from various professionals' and organisational perspectives are lacking. The aim of this study was therefore to explore various professionals' experiences of involvement in FD in order to get comprehensive understanding of the organisation, responsibilities and roles. Methods:This qualitative study is a part of a larger project with an action research approach focusing on FD in the municipal home service and care for home-living elderly persons in a munic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
0
9
0
1
Order By: Relevance
“…This is confirmed by results from other studies were it is shown that relatives of the municipal FS service users advocate a food preparation service in the home of the recipient reasoning that food preparation at home creates a real sense of homemade food and of being at home. Further, the studies highlighted the importance of the social aspects of the new FS that relieves loneliness and isolation among the recipients living alone and without frequent contact with other people (Pajalic, 2013c;Pajalic et al, 2012b). Another study showed that an individual's experiences are important because these experiences in combination with those of the FS personnel are important when promoting a holistic view on nutrition and better quality of life for individuals requiring help with meal preparation needs related to food intake (Odencrants, 2008).…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is confirmed by results from other studies were it is shown that relatives of the municipal FS service users advocate a food preparation service in the home of the recipient reasoning that food preparation at home creates a real sense of homemade food and of being at home. Further, the studies highlighted the importance of the social aspects of the new FS that relieves loneliness and isolation among the recipients living alone and without frequent contact with other people (Pajalic, 2013c;Pajalic et al, 2012b). Another study showed that an individual's experiences are important because these experiences in combination with those of the FS personnel are important when promoting a holistic view on nutrition and better quality of life for individuals requiring help with meal preparation needs related to food intake (Odencrants, 2008).…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…For this study manifest content analysis was used for analysis of the transcribed interview texts and notes from the participant observations (Krippendorff, 2004;Pajalic, Persson, Westergren, Berggren, & Skovdahl, 2012;Pajalic, Persson, Westergren, & Skovdahl, 2012b;Spradley, 1980). Qualitative content analysis is an interpretation process that focuses on similarities and differences in various parts of the transcribed text (Krippendorff, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…the various professionals' roles and responsibilities from being involved in FD (Pajalic, et al, 2012a) 2. the elderly persons experiences of receiving food distributed by the FD service (Pajalic, et al, 2012b) 3. participation based intervention for improving FD practice (Pajalic, et al, 2012c) 4. DM's views on the FD service and suggestions for which areas should be taken into consideration as starting points for changing the FD process and practice which was the subject of the first part of the present study.…”
Section: Data Collectionmentioning
confidence: 99%
“…Food was produced at a municipality owned kitchen. The diet manager had the overall responsibility for the food production and the personnel employed at the kitchens (Pajalic, Persson, Westergren, Berggren, & Skovdahl, 2012b;Pajalic, Persson, Westergren, & Skovdahl, 2012a). The municipal kitchen is subordinate to the municipal care and service administration which is led by the administrative manager who in turn is subordinate to the management committee represented by politicians (elected citizens' representatives, n=23).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation